Pharmaceutical-Oriented Methoxylation of Aryl C(sp2)–H Bonds using Copper Catalysts - Zhang, Guofu; Zhu, Jianfei; Tong, Chaolai; Ding, Chengrong (Synlett, 2018)
A pharmaceutical-oriented, copper(II)-catalyzed methoxylation of aryl C(sp2)–H bonds has been developed. This simple and environmentally benign reaction system occurs efficiently using oxygen as oxidant with broad substrate scope and high functional group tolerance.
Keywords: pharmaceutical development; C–H methoxylation; copper catalysis; oxygen; DMEDA